Rumah kutai - Natashah Md. Nor; Rusli Harun; Fauzi Daud (Malaysia : UAS Communications (M), 1997)
The arts of building Rumah Kutai in Perak, the house built without a single nail.
Executive producer, Najib Shafion, Zabidi Sanip ; script, Muhaimin Yusof
Narrator: Reemy Abdul Rahman
Keywords: Architecture, Domestic -- Perak; Malays -- Dwellings; Housing -- Perak